Parallel coupled cavity structure with constant magnets focusing system - Pavlov, V.M.; Shiyankov, S.V.; Ivannikov, V.I.; Chernousov, Yu.D.; Shebolaev, I.V. (Вопросы атомной науки и техники, 2001)
Accelerator for intensive electron beam (average current up to 2 A) from energy 50 keV up to energy 3-5 MeV is offered. Accelerating structure consist of a few resonators fed parallel from one waveguide. Focusing system contains constant radial magnets located between accelerating resonators and creating the axial alternating-gradient focusing magnetic field. Geometry and results of beam dynamics calculation such kind accelerator are presented.